Elusive elapids: biogeographic venom variation in Indian kraits and its repercussion on snakebite therapy - Rashmi, U.; Bhatia, Siddharth; Nayak, Muralidhar; Khochare, Suyog; Sunagar, Kartik (Frontiers in Pharmacology, 2024)
Snakebite is a major public health concern in many parts of the world, including India, where over 58,000 deaths occur annually due to snake envenoming. The common krait (Bungarus caeruleus) is responsible for the second-highest number of snakebite-related mortalities in the country. However, despite its notoriety, little is known about its venom ecology, functions and compositional variation across bioclimatic zones, partly because these nocturnal snakes are highly elusive, making it difficult to find them in the wild. We aim to address this knowledge gap by characterising the venom composition and toxicity profiles of the pan-Indian populations (n=8) of B. caeruleus using a combination of proteomics, receptor-toxin interaction assays, biochemical experiments, pharmacological tests and preclinical evaluations. We reveal considerable variation in venom composition, functions, and pharmacological activities among the geographically distinct populations of B. caeruleus. Furthermore, toxin-receptor interaction assays provide insights into their feeding ecology and prey-predator interactions. Finally, in vitro and in vivo experiments revealed the poor neutralising potencies of Indian antivenoms towards most populations of the common krait. Our findings highlight the alarming need to develop efficacious snakebite therapy in India to treat bites from this medically most important elapid snake.